Job satisfaction measurement scale - Álvarez Velázquez, Edalid; Vargas Hernández, Adriana Nicole; Martínez Sánchez, Cesar Enrique (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The research proposes a methodological design of a scale that allows knowing the degree of job satisfaction in Small and Medium Enterprises (SMEs). It is based on Herzberg’s theory of hygiene and motivation. It is made up of 15 items. The clarity and relevance of the items was validated with five experts. For its validity and reliability, a KMO master adequacy of .863 was obtained. The results were found to be significant (X2 = 441.790, df = 105, p = .000). Cronbach’s alpha was equal to .906. The test exercise is carried out in SMEs in Tuxpan Veracruz, Mexico.